Measurement Of The Success Of Accurate-5 Accounting Application Implementation In Human Organization Technology (HOT)-FIT Model Using Smartpls Software: Case Study Of D3 Accounting Computerization Students Of STMIK Mardira Indonesia Bandung - Amijaya, Hasanah Tisna (Jurnal Computech & Bisnis (e-journal), 2025)
The accounting application Accurate-5 provides benefits, including exceptional accuracy, ease of use, multicurrency functionality, and language support (English and Indonesian), appealing to users.  Organizations strive to optimize the utilization of application systems to their objectives.  Consequently, evaluating user preparedness is essential.  The Human Organisation Technology (HOT)-FIT model elucidates critical elements of application implementation and assesses user preparedness.  This paradigm comprises four elements: individuals, organization, technology, and the equilibrium of these elements, offering a straightforward yet thorough methodology. This study uses the HOT FIT methodology to evaluate the effectiveness of Accurate-5 implementation among D3 Accounting Computerisation students at STMIK Mardira Indonesia.  This method encompasses seven attributes: System Quality, Information Quality, Service Quality, System Users, User Satisfaction, and Benefits.  A questionnaire was administered to 58 students from the 2022 and 2023 cohorts.  The research findings indicate that Cronbach’s alpha and composite reliability values exceed 0.7, with an SRMR of 0.091 (below 0.10) and an NFI of 0.436 (below 0.9), suggesting that the model adequately fits the data.  Hypothesis analysis identifies four significant impacting variables, whilst four others exert no impact.